50 Genetics Ideas You Really Need to Know - Mark Henderson (Quercus, 2008)
In recent years knowledge of our genetic code has changed our understanding of life on Earth. New genetic technologies are transforming the way we live and promise treatments for otherwise incurable diseases. But these advances are also generating controversy, particularly surrounding issues such as cloning and designer babies. In \50 Genetics Ideas\, Mark Henderson distils the central ideas of genetics in a series of clear and concise essays. Beginning with the theory of evolution, and covering such topics as the genome and how nature and nurture work together, he not only illuminates the role of genes in shaping our behaviour and sexuality, but also the very latest, cutting-edge developments in gene therapy and artificial life. Accessible and informative, \50 Genetics Ideas\ is a timely introduction to this young and ground-breaking strand of science.